Development of Financial Literacy-Integrated Problem-Based Learning Worksheets for Enhancing Students’ Mathematical Problem-Solving Skills - Thurifqoh, Afifa; Sri Hastuti Noer; Agung Putra Wijaya (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop and evaluate financial literacy-integrated Problem-Based Learning (PBL) worksheets to foster students’ mathematical problem-solving skills. The product was developed using the ADDIE framework within a Research and Development (R&D) method, encompassing the stages of analysis, design, development, implementation, and evaluation. The field trial involved 61 eleventh-grade students, comprising 31 students in the experimental group and 30 in the control group, selected through cluster random sampling using a pretest–posttest control group design. Data were collected through expert validation, practicality questionnaires, and mathematical problem-solving tests. The data were analyzed using Aiken’s V to quantify expert judgments, item validity and reliability analyses to evaluate the mathematical problem-solving test, percentage analysis to assess practicality, normalized gain (N-gain) to measure improvements in mathematical problem-solving skills, and an independent-samples t-test to examine differences in improvement between the experimental and control groups. Expert judgments yielded Aiken’s V coefficients ranging from 0.84 to 0.93, indicating strong agreement among the experts regarding the relevance of the assessed components. The mathematical problem-solving test demonstrated acceptable item validity and good internal consistency, with a Cronbach’s alpha coefficient of 0.853. The developed worksheets demonstrated a high level of practicality, based on teacher and student response rates of 89% and 87.6%, respectively. The experimental group achieved a higher mean N-gain score (0.625) than the control group (0.516), with a statistically significant difference in improvement (one-tailed p = 0.011). These findings indicate that the developed financial literacy-integrated PBL worksheets meet established quality criteria, support classroom implementation, and foster students’ mathematical problem-solving skills through authentic financial contexts.